2003
DOI: 10.1111/j.1463-5224.2003.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antibiotic resistance in equine bacterial ulcerative keratitis (1991–2000): 65 horses

Abstract: Streptococcus equi subspecies zooepidemicus and Pseudomonas aeruginosa were the most common organisms isolated from cases of equine bacterial keratitis referred to the University of Florida's VMTH for the years 1991-2000. There appears to be an increase in resistance of Streptococcus equi subspecies zooepidemicus to gentamicin over the past 10 years. In addition, there is a significant increase in resistance of Pseudomonas aeruginosa to both gentamicin and tobramycin over the same time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
131
4
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(160 citation statements)
references
References 10 publications
18
131
4
7
Order By: Relevance
“…Pseudomonas spp. is a gram-negative bacillus, considered as one of the most virulent pathogens of the cornea, with a prevalence between 6 and 14% among the microorganisms identified in corneal ulcers of horses (SAUER et al, 2003;KELLER & HENDRIX, 2005;WADA et al, 2010;WADA et al, 2010). As expected, this genus was not isolated in the present study; although, it was previously identified in the eyes of horses without ophthalmic problems (ANDREW et al, 2003;VIDAL et al, 2010;JOHNS et al, 2011).…”
Section: Resultscontrasting
confidence: 40%
See 3 more Smart Citations
“…Pseudomonas spp. is a gram-negative bacillus, considered as one of the most virulent pathogens of the cornea, with a prevalence between 6 and 14% among the microorganisms identified in corneal ulcers of horses (SAUER et al, 2003;KELLER & HENDRIX, 2005;WADA et al, 2010;WADA et al, 2010). As expected, this genus was not isolated in the present study; although, it was previously identified in the eyes of horses without ophthalmic problems (ANDREW et al, 2003;VIDAL et al, 2010;JOHNS et al, 2011).…”
Section: Resultscontrasting
confidence: 40%
“…were identified here, and previously isolated in horses with and without ocular pathologies (KELLER & HENDRIX, 2003;ANDREW et al, 2003;JOHNS et al, 2011;TAMARZADEH & ARAGHI-SOOREH, 2014). Both Streptococcus and Serratia are commensal microorganisms of the ocular conjunctiva of horses, but can become pathogenic and trigger diseases when colonizing wounds (SAUER et al, 2003;VIDAL et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies are available on the development of antibiotic resistance of bacteria in horses. Sauer et al (2003) described an increased resistance to antibiotics in bacteria causing ulcerous keratitis in horses from 1991 to 2000. However, more frequent are studies which compare their results on antibiotic resistance with those published previously.…”
Section: Discussionmentioning
confidence: 99%